2006
DOI: 10.1038/sj.jes.7500475
|View full text |Cite
|
Sign up to set email alerts
|

Chlorpyrifos exposure in farm families: Results from the farm family exposure study

Abstract: We used urinary biological monitoring to characterize chlorpyrifos (O,O-diethyl-O-(3,5,6-trichloro-2-pyridinyl) phosphororthioate) exposure to farm family members from Minnesota and South Carolina who participated in the Farm Family Exposure Study. Five consecutive 24-h urine samples were obtained from 34 families of licensed pesticide applicators 1 day before through 3 days after a chlorpyrifos application. Daily 3,5,6-trichloro-2-pyridinol (TCP) urinary concentrations characterized exposure profiles of the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
46
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 11 publications
6
46
2
Order By: Relevance
“…6,25,26 However, the time for chlorpyrifos ADD A as represented by urinary TCP to decline to the baseline level differed from that observed in previous studies. With Sri-Lankan and USA farmers, this decline to baseline occurred in approximately 96 h 6,25,26 ).…”
Section: Post-application Exposure Levels Of Chlorpyrifos (Add a )mentioning
confidence: 68%
See 1 more Smart Citation
“…6,25,26 However, the time for chlorpyrifos ADD A as represented by urinary TCP to decline to the baseline level differed from that observed in previous studies. With Sri-Lankan and USA farmers, this decline to baseline occurred in approximately 96 h 6,25,26 ).…”
Section: Post-application Exposure Levels Of Chlorpyrifos (Add a )mentioning
confidence: 68%
“…6,25,26 However, the time for chlorpyrifos ADD A as represented by urinary TCP to decline to the baseline level differed from that observed in previous studies. With Sri-Lankan and USA farmers, this decline to baseline occurred in approximately 96 h 6,25,26 ). The recent study conducted by Farahat et al 24 indicated that urinary TCP concentration returned to the baseline level in excess of 168 h post application among Egyptian cotton farmers.…”
Section: Post-application Exposure Levels Of Chlorpyrifos (Add a )mentioning
confidence: 68%
“…2003, Hore et al, 2005Morgan et al 2005) have, on average, urinary TCPy values in the range of 6-8 ppb, or approximately 2-3 times greater than the "background" levels seen in the NHANES II study. Similarly, farmers who applied chlorpyrifos tended also to have urinary TCPy values about twofold greater than the NHANES II "background" levels, suggesting that some exposure to chlorpyrifos does occur (Curwin et al, 2005;Alexander et al, 2006). However, exposures to farm worker families in those same studies did not appear to add substantially to the background levels of TCPy in urine.…”
Section: Vc Specific Pathways Of Exposure Vc1 Urinary Tcpy As Amentioning
confidence: 79%
“…Because this study collected 24-h urine samples rather than spot urine samples, from farmers who applied chlorpyrifos, as well as from their spouses and children, and samples were collected prior to, the day of, and 3 days following application, it represents the most thorough and relevant assessment of chlorpyrifos exposures to date. The results of this exposure assessment study for chlorpyrifos were presented recently (Alexander et al, 2006) and are discussed later.…”
Section: Vb7 Farm Family Exposure Study (Ffes): Iowa and Southmentioning
confidence: 99%
“…Its presence in urine is regarded as a specific marker for exposure to these compounds in the occupational setting, although in the general population it is also a marker for direct exposure to TCPy, mostly from TCPy in food (Morgan et al, 2005). Urinary TCPy is used to assess exposure to CPF in the population at large (Barr et al, 2005;CDC, 2005) and among applicators and their families (Alexander et al, 2006). Urinary TCPy has been measured in epidemiological studies of children (Berkowitz et al, 2004;Eskenazi et al, 2004Eskenazi et al, , 2007, pesticide applicators (Steenland et al, 2000) and manufacturers (Albers et al, 2004a).…”
Section: Introductionmentioning
confidence: 99%